Achieving organisational efficiency through risk management / Irzan Ismail - Ismail, Irzan (2004)
Definitions of risk are very wide and it is usually defined or determined according to the environment or situation. The main definition of risk is the possibility of loss due to different hazards. There are physical hazard and moral hazards. Every department is exposed to numerous risks, as risk is well known of its existence in all conditions. Those risks that can be insured could be transferred to the insurance company or managed by the risk management department. But there are still those risks, which are uninsurable and normally related to moral hazard. The functions of risk management department are wide but due to certain factors its operation is quite limited. They are more towards handling of major risks. The main problem now is to identify what are those risks faced and how does each department response to these uninsurable risks. The main focus is to measure the understanding and awareness of the organisation and on the issue of risk management and how they perceived risk. However, the main purpose is to emphasize on the degree of impact of effective risk management process which is practised by or within the departments in relation to their behavior, mindset, level of acceptance decision making and motivation. These are subjective elements that support the risk management process. Control of risk can help minimize the probability of loss and interruption. It also helps in enhancing the business development towards a success.